Low-temperature and atmospheric pressure depolymerization method of waste polyester and its regeneration application
Patent Information
- Application Number
- CN202610969918.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这一技术路径同样面临产业化瓶颈:首先,所述有机碱催化剂普遍价格昂贵,其高昂的消耗成本极大地削弱了回收过程的经济可行性;其次,为保证有机碱的催化活性和对聚酯纤维的溶胀效果,该体系必须依赖乙腈、二甲基亚砜(DMSO)或二氯甲烷等高极性、非质子的有机溶剂,这些溶剂大多具有显著的毒性、难以生物降解,且因沸点、共沸等特性而极难通过简单的蒸馏实现高纯度回收与闭环循环,不仅增加了生产成本,更带来严峻的环境合规压力
本发明采用“无机碱水溶液+季铵盐相转移催化剂”与“环状碳酸酯-醇类化合物”复配溶剂体系相协同的技术方案,从根本上解决了传统工艺中有机碱催化剂成本高昂、溶剂高毒性难回收、无机碱催化效率低等问题。
Smart Images

Figure CN123003397A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical recycling technology of polymer materials, specifically to a low-temperature atmospheric pressure depolymerization method for waste polyester, and a method for preparing recycled polyethylene terephthalate from the recycled products. Background Technology
[0002] With the widespread use of polyester (PET) materials in textiles, packaging, and other fields, the stock of waste polyester is growing rapidly. Efficient and green recycling of PET has become a key issue for the global textile and materials industry to achieve sustainable development. Compared to simple physical recycling, chemical recycling, by depolymerizing polyester into monomers such as terephthalic acid (TPA) or dimethyl terephthalate (DMT), can achieve a closed-loop "fiber-to-fiber" cycle, and is therefore considered a fundamental way to improve resource utilization efficiency.
[0003] Currently, chemical depolymerization technologies for waste polyester are developing along two main paths. The first is solvent-assisted high-temperature, high-pressure alkaline or alcoholysis processes. These methods typically use ethylene glycol or high-concentration inorganic alkalis, reacting at temperatures ranging from 180°C to 260°C or even higher, and require pressure-bearing equipment. Although the technology is mature, the high-temperature, high-pressure conditions bring significant energy consumption and safety hazards. Furthermore, under harsh conditions, byproducts are easily generated, affecting the purity and color value of the recovered monomers. The corrosion of equipment by the reaction system is also a significant concern.
[0004] To overcome the drawbacks of high temperature and high pressure, the second technical approach aims to achieve depolymerization at low temperature (typically <120℃) and normal pressure, and introduces organic bases as the main catalyst for this purpose. In this type of process, the use of strongly basic organic compounds such as amidines, guanidines, or phosphazenes can catalyze the breaking of ester bonds under relatively mild conditions. However, this technical approach also faces industrialization bottlenecks: First, the organic base catalysts are generally expensive, and their high consumption costs greatly reduce the economic feasibility of the recovery process; second, to ensure the catalytic activity of the organic base and the swelling effect on polyester fibers, the system must rely on highly polar, aprotic organic solvents such as acetonitrile, dimethyl sulfoxide (DMSO), or dichloromethane. These solvents are mostly highly toxic, difficult to biodegrade, and due to their boiling points, azeotropic properties, etc., it is extremely difficult to achieve high-purity recovery and closed-loop recycling through simple distillation, which not only increases production costs but also brings severe environmental compliance pressure.
[0005] Although the industry has attempted to add small amounts of inexpensive inorganic bases (such as sodium hydroxide) as auxiliary catalysts in these low-temperature processes to reduce costs, the long-standing issue is that inorganic bases have limited dissociation in reaction media dominated by organic solvents, and hydroxide ions struggle to cross the aqueous / organic phase interface and fully contact the polyester surface. This results in extremely low catalytic efficiency when used alone, making it completely unsuitable for supporting economical and efficient depolymerization reactions. This technological bias has meant that inorganic bases have consistently played only an inefficient supporting role in the field of low-temperature atmospheric pressure depolymerization, failing to resolve the fundamental contradiction between catalyst cost and solvent environmental friendliness.
[0006] In summary, existing technologies urgently need a novel chemical recycling solution for waste polyester that can fully utilize the high-efficiency catalytic potential of inexpensive inorganic bases while eliminating dependence on highly toxic aprotic organic solvents, thereby achieving high efficiency, low cost, and fully green recycling at low temperature and ambient pressure. Summary of the Invention
[0007] To solve the above-mentioned technical problems, a first aspect of the present invention provides a method for low-temperature atmospheric pressure depolymerization of waste polyester, comprising: Waste polyester raw materials are mixed with an inorganic alkaline aqueous solution, a quaternary ammonium salt phase transfer catalyst, and a compound solvent to form a reaction mixture; the compound solvent contains cyclic carbonates and alcohol compounds. Under conditions of temperature ≤110℃ and normal pressure, the reaction mixture is subjected to a depolymerization reaction to generate terephthalate and ethylene glycol.
[0008] In a preferred embodiment of the present invention, the inorganic base is sodium hydroxide or potassium hydroxide; the cyclic carbonate is a five-membered cyclic carbonate.
[0009] In a preferred embodiment of the present invention, the five-membered cyclic carbonate is selected from at least one of propylene carbonate and ethylene carbonate; in the compound solvent, the mass ratio of the five-membered cyclic carbonate to the alcohol compound is 1.6:1 to 1.7:1.
[0010] In a preferred embodiment of the present invention, the alcohol compound is selected from at least one of ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, n-hexanol, ethylene glycol, 1,2-propanediol, and 1,3-propanediol.
[0011] In a preferred embodiment of the present invention, the mass percentage concentration of the inorganic alkali aqueous solution is 10% to 15%; the mass ratio of the inorganic alkali in the inorganic alkali aqueous solution to the mass of the quaternary ammonium salt phase transfer catalyst is 50:1 to 80:1.
[0012] In a preferred embodiment of the present invention, the mass ratio of the compound solvent to the waste polyester raw material is 3:1 to 5:1.
[0013] In a preferred embodiment of the present invention, the quaternary ammonium salt phase transfer catalyst is selected from one or more of hexadecyltrimethylammonium bromide, tetrabutylammonium bromide, and benzyltriethylammonium chloride.
[0014] In a preferred embodiment of the present invention, the temperature of the depolymerization reaction is 70°C to 90°C, and the reaction time is 1 to 3 hours.
[0015] In a preferred embodiment of the present invention, the depolymerization reaction is carried out under ultrasonic conditions; preferably, the ultrasonic conditions include: immersing an ultrasonic probe in the reaction solution and applying ultrasonic waves at a frequency of 20~30kHz.
[0016] In a preferred embodiment of the present invention, the mass ratio of the waste polyester raw material to the compound solvent and the quaternary ammonium salt phase transfer catalyst is 1:6 to 1:8.
[0017] In a preferred embodiment of the present invention, the method further includes: acidifying the obtained terephthalate using hydrochloric acid or sulfuric acid, controlling the endpoint pH to be 1-3, to obtain terephthalic acid; and after the depolymerization reaction is completed, separating the alcohol compound by distillation, then separating the cyclic carbonate, and recycling it for the preparation of the compound solvent.
[0018] A second aspect of the present invention provides a method for preparing recycled polyethylene terephthalate, comprising: Terephthalic acid is obtained by the method described in the first aspect of the present invention; the terephthalic acid is polymerized with ethylene glycol to obtain recycled polyethylene terephthalate; and the recycled polyethylene terephthalate is then spun.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention employs a synergistic technical solution combining an "inorganic alkali aqueous solution + quaternary ammonium salt phase transfer catalyst" with a "cyclic carbonate-alcohol compound" composite solvent system, fundamentally solving the problems of high cost of organic alkali catalysts, high toxicity and difficulty in solvent recovery, and low catalytic efficiency of inorganic alkali in traditional processes.
[0020] Specifically, this invention utilizes a quaternary ammonium salt phase transfer catalyst to break down the mass transfer barrier between the aqueous and organic phases, enabling hydroxide ions to efficiently enter the organic solvent system and penetrate into the interior of PET fibers to attack ester bonds. At the same time, the cyclic carbonates in the compound solvent effectively swell the PET, and the alcohol compounds adjust the polarity and viscosity of the system. The combined effect of these two factors achieves efficient depolymerization of waste polyester under conditions of ≤110℃ and normal pressure.
[0021] Most importantly, the components in the compound solvent have significant differences in boiling point, which can be recovered and recycled with high purity through simple distillation. This makes the entire process route have the outstanding advantages of low cost, low energy consumption, green environmental protection, and suitability for large-scale industrial production.
[0022] Other features and beneficial effects of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other beneficial effects of the invention can be realized and obtained by means of the structures particularly pointed out in the description, claims and drawings. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Unless otherwise specified, the positional relationships shown in the drawings in the following description are based on the direction in which the components are drawn in the figure.
[0024] Figure 1 A photograph of the product TPA from Example 1 of this invention. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. The technical features designed in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0026] In the description of this invention, it should be noted that all terms used in this invention (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains, and should not be construed as limiting the invention; it should be further understood that the terms used in this invention should be understood to have the same meaning as those in the context of this specification and in the relevant field, and should not be understood in an idealized or overly formal sense, except as expressly defined in this invention.
[0027] Those skilled in the art will understand that the order in which the steps are written in the various implementations or embodiments does not imply a strict execution order and does not constitute any limitation on the implementation process. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps in this application can be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps 1 and 2, it means that the method may include steps 1 and 2 performed sequentially, or it may include steps 2 and 1 performed sequentially. For example, if the method may also include step 3, it means that step 3 can be added to the method in any order. For example, the method may include steps 1, 2, and 3, or it may include steps 1, 3, and 2, or it may include steps 3, 1, and 2, etc.
[0028] The first aspect of the present invention provides a method for low-temperature atmospheric pressure depolymerization of waste polyester, comprising the following steps: Step 1: Mix waste polyester raw materials with inorganic alkaline aqueous solution, quaternary ammonium salt phase transfer catalyst and compound solvent to form a reaction mixture; the compound solvent contains cyclic carbonates and alcohol compounds; Step 2: Under normal temperature and pressure conditions, the reaction mixture is subjected to a depolymerization reaction to generate terephthalate and ethylene glycol.
[0029] In a preferred embodiment of the present invention, the method further includes step 3: acidifying the obtained terephthalate to obtain terephthalic acid; and a solvent recovery step: after the depolymerization reaction is completed, the alcohol compound is first separated by distillation, and then the cyclic carbonate is separated and recycled for the preparation of the compound solvent.
[0030] Regarding step 1, it should be noted that the "waste polyester raw materials" mentioned in this invention refer to post-consumer or industrially waste polyethylene terephthalate (PET) products, including but not limited to pure polyester fabrics, polyester blended fabrics, waste polyester clothing, polyester industrial yarns and their products, waste polyester bottle flakes, etc. The form of the waste polyester raw materials is not limited to powder; it can also be fragments, fiber clumps, granules, etc., after cutting, crushing, and loosening. This invention is particularly suitable for polyester fabrics with an intrinsic viscosity of 0.65–0.80 dL / g. This viscosity range corresponds to textile polyester with a certain degree of crystallinity and orientation. Traditional mild depolymerization methods are difficult to achieve efficient degradation, while the catalytic-solvent system of this invention can effectively overcome this structural barrier.
[0031] In this invention, the inorganic base constitutes the main catalyst for the depolymerization reaction, and its role is to provide highly active hydroxide ions (OH-). -The inorganic base acts as a nucleophile, attacking the carbonyl carbon in the ester chain of PET molecules and initiating the breakage of the ester bond. The inorganic base is preferably sodium hydroxide or potassium hydroxide, more preferably sodium hydroxide, because it is extremely inexpensive, widely available in industrial applications, and its basicity is sufficient to exert a highly efficient catalytic effect in the compound solvent system. It should be noted that the inorganic base is used in the form of an aqueous solution, rather than being added directly in solid form. The importance of this method lies in: First, pre-preparing the solution as an aqueous solution ensures uniform dispersion of the alkali in the reaction system, avoiding side reactions or yellowing of the product due to excessively high local concentrations. Second, the presence of an appropriate amount of water in the system is a necessary condition for the quaternary ammonium salt phase transfer catalyst to function effectively; the aqueous phase acts as the OH-... - The initial storage and transfer source.
[0032] Further, the mass percentage concentration of the inorganic alkaline aqueous solution is preferably 10% to 15%. For example, the concentration can be 10%, 11%, 12%, 13%, 14%, 15%, or any value between them. If the concentration is less than 10%, the OH- in the aqueous phase will... - Insufficient effective concentration weakens the mass transfer driving force, leading to a decrease in the depolymerization rate; if the concentration is higher than 15%, the system water content is too low, which is not conducive to the precipitation or phase separation of inorganic base in the solvent system, and may also aggravate side reactions of the product. Within this concentration window, the phase transfer efficiency of the quaternary ammonium salt phase transfer catalyst is related to OH... - The supply rate can be optimized.
[0033] In this invention, the quaternary ammonium salt phase transfer catalyst is the core component for achieving efficient low-temperature depolymerization. It should be noted that the quaternary ammonium salt used is a cationic surfactant, possessing both hydrophilic and lipophilic properties. Its mechanism of action is dual: firstly, as a typical phase transfer catalyst, its cationic portion, through the hydrophobic interaction of its long-chain alkyl group, can depolymerize OH groups in the aqueous phase. - It continuously "carries" and transfers to the organic solvent system in the form of ion pairs, thereby penetrating into the interior of the PET fiber crystalline layer, completely breaking down the mass transfer barrier between the aqueous and organic phases, allowing OH... - It can fully contact and react with ester bonds; through extensive experiments, this invention has found that for polyester fabrics with an intrinsic viscosity of 0.65 to 0.80 dL / g, when the mass ratio of inorganic alkali to quaternary ammonium salt phase transfer catalyst in the inorganic alkali is controlled at 50:1 to 80:1, the phase transfer catalytic efficiency and depolymerization reaction rate can reach a better balance, which is beneficial to improving the depolymerization efficiency of PET and obtaining high-purity terephthalic acid products.
[0034] It should be further noted that the types of quaternary ammonium salts used include, but are not limited to, hexadecyltrimethylammonium bromide (CTAB), tetrabutylammonium bromide (TBAB), and benzyltriethylammonium chloride (TEBA). Furthermore, compared to the more expensive quaternary phosphonium salts, quaternary ammonium salts are more suitable for low-temperature liquid-phase mild depolymerization systems, while quaternary phosphonium salts are typically used in high-temperature deep melt depolymerization. Therefore, under the low-temperature, atmospheric-pressure process conditions of this invention, quaternary ammonium salts are the preferred option for achieving a balance between economy and efficiency.
[0035] In this invention, the compound solvent comprises cyclic carbonates and alcohols, which is another core technology for achieving green, recyclable, and low-temperature depolymerization.
[0036] The cyclic carbonate is preferably a five-membered cyclic carbonate, more preferably selected from at least one of propylene carbonate (PC) and ethylene carbonate (EC). PC is a liquid at room temperature, has good fluidity, is easy to handle, and is more conducive to industrial applications. EC has higher polarity than PC and stronger swelling ability for PET, but its freezing point is higher (about 36°C), and it is a solid at room temperature. It needs to be heated and kept warm during use to prevent crystallization and blockage of pipelines. Compared with PC, its usage conditions are more stringent. In addition, due to the excessively high polarity of EC, it is more likely to cause the quaternary ammonium salt phase transfer catalyst to deactivate due to excessive solvation. Therefore, in scenarios where maximizing catalyst activity is required, PC is more conducive to maintaining the stable operation of the catalytic system. In this invention, the term "five-membered cyclic carbonate" actually only covers a few types of hydrocarbon carbonates such as PC and EC that have similar structures and functions.
[0037] The alcohols are selected from at least one of ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, n-hexanol, ethylene glycol, 1,2-propanediol, and 1,3-propanediol. The alcohols in this specific list have boiling point ranges from 78.3°C (ethanol) to 214°C (1,3-propanediol), but all have sufficiently large boiling point differences with the selected cyclic carbonates (PC boiling point 238°C, EC boiling point 248°C) to ensure effective separation and high-purity recovery of both after depolymerization via conventional distillation. This is a fundamental prerequisite for achieving a closed-loop solvent cycle, reducing production costs, and minimizing environmental footprint. Particularly preferred is isopropanol (IPA), with a boiling point of 82°C, which has the most reasonable boiling point difference with PC and excellent solubility and viscosity adjustment capabilities.
[0038] The synergistic effect of the above-mentioned PC-IPA compound solvent system is reflected in the following three aspects: Firstly, PC possesses strong polarity and a high dielectric constant (approximately 65), far exceeding that of conventional organic solvents. This characteristic enables it to effectively swell and loosen the amorphous and partially crystalline regions of PET fibers, promoting the penetration of reactants into the polymer matrix. Simultaneously, PC's high polarity facilitates the dissociation of the quaternary ammonium salt phase-transfer catalyst Q. + X - This puts it in an activated ion state, making it suitable for catalytic cycles.
[0039] Secondly, the addition of IPA can play a triple regulatory role: ① reduce the viscosity of the system and improve the efficiency of mass and heat transfer; ② moderately reduce the polarity of PC, avoid the deactivation of quaternary ammonium salt catalyst due to excessive solvation, improve the interfacial compatibility between the aqueous phase and the organic phase, and promote the interphase mass transfer process.
[0040] Third, after PC and IPA are compounded, the boiling point is controllable and the difference between the two boiling points is extremely large (IPA is about 82℃ and PC is about 238℃). After depolymerization, the solvent can be recovered by simple fractional distillation: first distill off IPA under normal pressure, and then distill off PC (and ethylene glycol) under reduced pressure, or vice versa. After the purity of the recovered solvent is restored, it can be reused to prepare compound solvents, thus realizing a true closed-loop cycle.
[0041] For step 2, in this invention, the temperature of the depolymerization reaction is controlled to ≤110℃, preferably 70℃~90℃, and more preferably 90℃. For example, the reaction temperature can be 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, or any value between them. Compared with the existing low-temperature depolymerization technology, which is typically applicable to a range of "room temperature to 120℃", this invention, through an innovative catalyst and solvent system, further narrows the upper limit to 110℃, achieving more efficient depolymerization at even lower temperatures. Temperatures above 110℃ may cause the TPA product to turn yellow due to side reactions, resulting in a decrease in purity. The ambient pressure condition is approximately 0.1 MPa, requiring no pressurization or pressure-resistant equipment, greatly reducing equipment investment and operational risks, and laying the foundation for continuous industrial production. The reaction time is preferably 1~3 hours, and the specific time can be adjusted according to the characteristics of the raw materials, the feed ratio, and the target depolymerization rate.
[0042] In a preferred embodiment of the present invention, the depolymerization reaction in step 2 is carried out under ultrasonic conditions. Specifically, the ultrasonic conditions are immersion ultrasound of the reaction system: in a jacketed temperature-controlled reactor, an ultrasonic probe is immersed in the reaction mixture, and ultrasonic waves are applied at a frequency of 20-30 kHz, with ultrasonic irradiation occurring continuously or intermittently over the 1-3 hours of the reaction. By utilizing the ultrasonic cavitation effect, local high-temperature and high-pressure hot spots and powerful microjets are generated in the reaction liquid phase, continuously cleaning and activating the PET fiber surface, constantly renewing the reaction interface, thereby significantly reducing interfacial mass transfer resistance. This physical-level enhancement, combined with the chemical carrying effect of the quaternary ammonium salt phase transfer catalyst, forms a physical-chemical dual mass transfer enhancement effect, synergistically achieving efficient and deep depolymerization below 110°C, and further reducing the catalyst dosage requirement or shortening the reaction time.
[0043] In a preferred embodiment of the present invention, the mass ratio of the waste polyester raw material to the total mass of the compound solvent, inorganic alkaline aqueous solution, and quaternary ammonium salt phase transfer catalyst is 1:6 to 1:12, for example, it can be 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, 1:10, 1:10.5, 1:11, 1:11.5, 1:12, or any value between them. This feed ratio ensures sufficient contact between the solid and liquid phases, ensuring uniformity of mass and heat transfer.
[0044] For step 3 and the solvent recovery step: After the depolymerization reaction is complete, the reactants are a solid-liquid mixture. Hot filtration is performed to remove incompletely depolymerized PET residue and other solid impurities. This hot filtration utilizes the system's low viscosity and good flowability at high temperatures to improve filtration efficiency and product yield. After cooling, terephthalic acid crystallizes out as disodium terephthalic acid. Acidification with dilute sulfuric acid or dilute hydrochloric acid converts the sodium terephthalic acid into free terephthalic acid (TPA). Further filtration, washing, and drying yield the purified TPA product.
[0045] The acidified mother liquor and distillate fraction contain solvent and ethylene glycol. A solvent recovery step utilizes the differences in boiling points of the components for separation: first, high-purity alcohols (such as IPA) are recovered by atmospheric distillation at approximately 80–83°C; then, cyclic carbonates (such as PC) and the reaction byproduct ethylene glycol (EG) are recovered by vacuum distillation at a lower temperature under reduced pressure. The recovered solvent can be replenished with fresh solvent as needed to prepare compound solvents, achieving recycling.
[0046] A second aspect of the present invention provides a method for preparing recycled polyethylene terephthalate, comprising: Step A: Obtain terephthalic acid using the method described in the first aspect of this invention; Step B: The terephthalic acid and ethylene glycol are subjected to a polymerization reaction to obtain recycled polyethylene terephthalate (rPET). Step C: The recycled polyethylene terephthalate is then spun.
[0047] For step A, the depolymerization and TPA purification processes involved have been fully described in the method of the first aspect of the invention and will not be repeated here. It should be emphasized that the TPA obtained by the method of the present invention has high purity (usually ≥98%), appears as white crystals, and fully meets the requirements for direct polymerization to prepare PET chips.
[0048] For step B, the polymerization reaction can be carried out using conventional PET polymerization processes in the art. Typically, TPA and ethylene glycol are first mixed in a certain molar ratio (e.g., 1:1.1 to 1:1.3) and esterified in an esterification reactor at 230–260°C to produce ethylene terephthalate (BHET) and its oligomers. Subsequently, the esterification product is transferred to a polycondensation reactor and polycondensed in the presence of a catalyst (such as antimony trioxide) under high temperature (270–290°C) and high vacuum (<100 Pa) conditions to remove ethylene glycol and obtain rPET melt or chips with a certain intrinsic viscosity.
[0049] In step C, the rPET chips are dried, melted, metered, and filtered, then extruded into fibers through a spinneret. These fibers then undergo conventional spinning processes such as cooling, oiling, drawing, setting, and winding to produce recycled polyester filaments or staple fibers. Due to the high purity of rTPA and the characteristics of the closed-loop recycling process, the resulting rPET fibers possess physical properties comparable to virgin PET fibers and can be reused in textiles, clothing, footwear, and other fields, achieving a closed-loop cycle.
[0050] As described above, the compound solvent used in this invention consists of cyclic carbonates (such as propylene carbonate) and alcohols (such as isopropanol). Both solvents are low-toxicity or slightly toxic substances, significantly reducing the harm to operators and the environment compared to commonly used highly toxic aprotic solvents (such as dimethyl sulfoxide, acetonitrile, and dichloromethane). More importantly, there is a significant boiling point difference between the cyclic carbonates and alcohols (e.g., propylene carbonate has a boiling point of approximately 238°C, and isopropanol has a boiling point of approximately 82°C). This physical characteristic allows for the sequential recovery of alcohols and cyclic carbonates through simple atmospheric and vacuum distillation after depolymerization, with sufficient purity for direct use in the preparation of solvents for the next depolymerization reaction. Thus, the compound solvent essentially achieves closed-loop recovery and reuse throughout the entire process cycle, significantly reducing the consumption of new solvent per unit volume and effectively avoiding the generation of large amounts of organic waste liquid, conforming to the atom economy principles of green chemistry and the requirements of industrial ecology.
[0051] Meanwhile, the sodium hydroxide aqueous solution, serving as the main catalyst, is extremely inexpensive, and the quaternary ammonium salt phase transfer catalyst, serving as a co-catalyst, is also a conventional industrial chemical, used in very small quantities. Compared to traditional routes that heavily rely on expensive organic bases (such as phosphazene bases and DBU), this significantly reduces overall reagent costs. The entire depolymerization process is carried out at a low temperature not exceeding 110°C and at normal pressure, eliminating the need for pressure-bearing equipment. This reduces fixed asset investment and lowers the safety risks associated with high-temperature and high-pressure operations, thus demonstrating significant industrialization advantages in both technical and economic aspects and environmental friendliness.
[0052] The following describes embodiments of the present invention. These embodiments are exemplary and are only used to explain the present invention, and should not be construed as limiting the invention. Where techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0053] Example 1 The recycled pure polyester shoe material was mechanically pulverized into powder (the intrinsic viscosity of the material is 0.67-0.72 dL / g). 100 parts by weight of this polyester powder were placed in a reaction vessel, and 250 parts by weight of propylene carbonate (PC), 150 parts by weight of isopropanol (IPA), 60 parts by weight of sodium hydroxide (prepared as a 12% (w / w) dilute aqueous solution, i.e., 440 parts by weight of deionized water), and 1 part by weight of quaternary ammonium salt phase transfer catalyst (tetrabutylammonium bromide TBABCAS: 1643-19-2 industrial grade) were added sequentially. The mixture was stirred to form a reaction mixture. The reaction vessel was heated to 105°C and stirred for 1 hour under normal pressure (approximately 0.1 MPa). After the reaction was completed, the mixture was filtered while hot to remove unreacted PET and impurities. After cooling, disodium terephthalate solid precipitated from the filtrate. Dilute sulfuric acid was added dropwise to acidify the filtrate, precipitating terephthalic acid (TPA). The precipitate was filtered, washed with deionized water until neutral, and dried to obtain the TPA product. Figure 1 The mother liquor is first distilled at atmospheric pressure to recover isopropanol, and then distilled under reduced pressure to recover propylene carbonate and the by-product ethylene glycol (EG).
[0054] Example 2 The procedure is essentially the same as in Example 1, except that immersion ultrasound is applied throughout the 1-hour incubation and stirring reaction. Specifically, an ultrasonic probe is inserted 12 cm below the surface of the reaction mixture from the top of the reactor, continuously outputting ultrasonic waves at a frequency of 25 kHz. All other operations and conditions remain unchanged.
[0055] Example 3 The process is basically the same as in Example 1, except that 250 parts by weight of propylene carbonate is replaced with an equal mass of ethylene carbonate (EC). Since EC is a solid at room temperature, the reaction system is preheated to 40°C to prevent crystallization from clogging the pipeline. Then it is heated to 105°C for the reaction. All other operations and conditions remain unchanged. Example 4 The method is basically the same as in Example 1, except that 150 parts by weight of isopropanol is replaced with an equal mass of the following alcohol compounds.
[0056] In Example 4a, ethanol was used; in Example 4b, n-butanol was used.
[0057] Example 5 The process is basically the same as in Example 1, except that the mass ratio of sodium hydroxide (in solid form) to quaternary ammonium salt is changed, while the rest of the formulation and operation remain the same.
[0058] In Example 5a, the mass ratio of sodium hydroxide to quaternary ammonium salt was 50:1; Example 5b: The mass ratio of sodium hydroxide to quaternary ammonium salt is 80:1.
[0059] Example 6 It is basically the same as Example 1, except that the reaction temperature and time are adjusted.
[0060] Among them, Example 6a: reaction temperature 70℃, reaction time 3 hours; Example 6b: reaction temperature 90℃, reaction time 1 hour.
[0061] Example 7 Waste polyester fabric with an intrinsic viscosity of 0.62 dL / g was selected, crushed, and depolymerized according to the same formula and operation as in Example 1.
[0062] Comparative Example 1 The recycled pure polyester shoe material was mechanically pulverized into powder (intrinsic viscosity same as in Example 1). 100 parts by weight of the polyester powder were placed in a reaction vessel, and 250 parts by weight of propylene carbonate, 150 parts by weight of isopropanol, and 60 parts by weight of sodium hydroxide (prepared as a 12% dilute aqueous solution) were added. No quaternary ammonium salt was added. The reaction vessel was heated to 105°C and reacted at atmospheric pressure for 1 hour. Subsequent treatment was the same as in Example 1.
[0063] Comparative Example 2 The recycled pure polyester shoe material was mechanically pulverized into powder (intrinsic viscosity same as in Example 1). 100 parts by weight of the polyester powder were placed in a reaction vessel, and 400 parts by weight of propylene carbonate, 60 parts by weight of sodium hydroxide (prepared as a 12% dilute aqueous solution), and 1 part by weight of a quaternary ammonium salt (same type as in Example 1) were added. Isopropanol was not added. The reaction vessel was heated to 105°C and reacted at atmospheric pressure for 1 hour. Subsequent treatment was the same as in Example 1.
[0064] Comparative Example 3 The recycled pure polyester shoe material was mechanically pulverized into powder (intrinsic viscosity same as in Example 1). 100 parts by weight of the polyester powder were placed in a reaction vessel, and 400 parts by weight of propylene carbonate, 60 parts by weight of sodium hydroxide (added directly in solid form), and 1 part by weight of quaternary ammonium salt (same type as in Example 1) were added. The reaction vessel was heated to 105°C and reacted at atmospheric pressure for 1 hour. Subsequent treatment was the same as in Example 1.
[0065] Comparative Example 4 The recycled pure polyester shoe material was mechanically pulverized into powder (intrinsic viscosity same as in Example 1). 100 parts by weight of the polyester powder were placed in a reaction vessel, and 250 parts by weight of propylene carbonate, 150 parts by weight of isopropanol, 60 parts by weight of sodium hydroxide (prepared as a 12% dilute aqueous solution), and 1 part by weight of a quaternary ammonium salt (same type as in Example 1) were added. The reaction vessel was heated to 130°C, and the reaction apparatus was equipped with a reflux condenser to reduce isopropanol volatilization loss. The reaction was carried out at atmospheric pressure for 1 hour, and subsequent treatment was the same as in Example 1.
[0066] Comparative Example 5 The recycled pure polyester shoe material was mechanically pulverized into powder (intrinsic viscosity same as in Example 1). 100 parts by weight of the polyester powder were placed in a reaction vessel, and 400 parts by weight of isopropanol (total solvent amount equivalent to that in Example 1), 60 parts by weight of sodium hydroxide (prepared as a 12% dilute aqueous solution), and 1 part by weight of quaternary ammonium salt (same type as in Example 1) were added. The reaction vessel was heated to 105°C and reacted at atmospheric pressure for 1 hour. Subsequent treatment was the same as in Example 1.
[0067] Comparative Example 6 The recycled pure polyester shoe material was mechanically pulverized into powder (intrinsic viscosity same as in Example 1). 100 parts by weight of the polyester powder were placed in a reaction vessel, and 400 parts by weight of isopropanol and 60 parts by weight of sodium hydroxide (prepared as a 12% dilute aqueous solution) were added. Propylene carbonate and quaternary ammonium salt were not added. The reaction vessel was heated to 105°C and reacted at atmospheric pressure for 1 hour. Subsequent treatment was the same as in Example 1.
[0068] Comparative Example 7 The process is basically the same as in Example 1, except that 150 parts by weight of isopropanol are replaced with acetonitrile, while the rest of the formulation and operation remain unchanged. Test case The products obtained from the above embodiments and comparative examples were subjected to the following tests: (1) PET depolymerization rate: After the reaction is complete, filter while hot, collect the insoluble filter residue, wash thoroughly, dry and weigh. Depolymerization rate (%) = (initial PET mass - residue mass) / initial PET mass × 100%; The test methods used are in accordance with GB / T 40006.9-2021; (2) TPA purity: determined by high performance liquid chromatography (HPLC), referring to GB / T30911-2014; (3) TPA Appearance: Visually observe the color and shape; (4) Solvent recovery rate: Collect the alcohol (or corresponding alternative solvent) and cyclic carbonate fractions recovered by distillation, weigh them, and the recovery rate (%) = recovered mass / initial input mass × 100%.
[0069] The test results for each group are summarized in the table below.
[0070] Table 1
[0071] According to the table above, we can find that: A comparison of Example 1 and Comparative Example 1 shows that, under the same conditions, the addition of a quaternary ammonium salt phase transfer catalyst increased the PET depolymerization rate from 60% to 100%, and the TPA purity from 85% to 99.5%. This fully demonstrates that the quaternary ammonium salt phase transfer catalyst can promote the migration of hydroxide ions from the aqueous phase to the polyester surface, reduce interfacial mass transfer resistance, and increase the ester bond breaking reaction rate. It is a core component for achieving low-temperature, atmospheric-pressure depolymerization. The applicant believes that the introduction of the quaternary ammonium salt phase transfer catalyst helps reduce the dependence of the depolymerization reaction on high-temperature conditions, enabling the system to obtain higher depolymerization efficiency and product purity at lower temperatures.
[0072] Among these factors, higher reaction temperatures make the product TPA more prone to yellowing, and impurities can affect its purity.
[0073] The comparison between Example 1 and Comparative Example 2 shows that when PC is used alone without isopropanol, the depolymerization rate drops to 75% and the purity drops to 90%, indicating that IPA plays a key regulatory role in the system, such as reducing viscosity, adjusting polarity, and preventing catalyst deactivation. It is an indispensable component of the compound solvent.
[0074] The applicant further argues that isopropanol can improve the interfacial compatibility between the aqueous phase, the polyester solid phase, and the organic phase, reduce the interfacial tension of the system, and promote a certain degree of swelling of the polyester molecular chains, thereby facilitating the diffusion of hydroxide ions into the polyester interior and improving the ester bond breaking efficiency. Therefore, isopropanol not only participates in the system construction as a compound solvent component but also has an interfacial promoting effect on the depolymerization process.
[0075] A comparison of Example 1 and Comparative Example 3 shows that when sodium hydroxide is added in solid form instead of being pre-prepared into a dilute aqueous solution, the depolymerization rate is only 80%, and the product is yellowish and its purity decreases. This indicates that introducing alkali in the form of a dilute aqueous solution is an important process measure to maintain the phase transfer catalytic cycle and avoid localized over-concentration side reactions.
[0076] The comparison between Example 1 and Comparative Example 4 shows that when the reaction temperature rises to 130℃, although the depolymerization rate remains 100%, the TPA purity drops significantly to 93%, and the product turns severely yellow. This demonstrates that controlling the temperature at ≤110℃ not only achieves efficient depolymerization but also effectively inhibits product deterioration and ensures the high quality of the recovered monomers.
[0077] The comparison between Example 1 and Comparative Examples 5 and 6 shows that when propylene carbonate is not added and only isopropanol and quaternary ammonium salt are used, the PET depolymerization rate decreases to 80%, and the TPA purity decreases to 85%. However, when neither propylene carbonate nor quaternary ammonium salt is added, the PET depolymerization rate drops significantly to 75%, and the TPA purity also drops significantly to 80%. This demonstrates that the use of propylene carbonate (PC) can improve the depolymerization effect and increase product purity; moreover, the use of PC and quaternary ammonium salt has a synergistic effect, and when both are absent, the PET depolymerization ability and product purity will deteriorate drastically.
[0078] The comparison between Example 1 and Comparative Example 7 shows that when a non-alcoholic organic solvent is used instead of isopropanol, the depolymerization rate drops significantly to 60%, and the TPA purity also drops significantly to 80%. This demonstrates that using alcohols, especially isopropanol, as a compound solvent component can improve the PET depolymerization rate and TPA purity compared to non-alcoholic organic solvents.
[0079] Application examples The high-purity rTPA obtained in Example 1 was repolymerized with recycled ethylene glycol (EG). rTPA and EG were added to an esterification reactor at a molar ratio of 1:1.2 and esterified at 250°C and atmospheric pressure until the water content reached the theoretical value. Then, antimony trioxide (0.03% of TPA mass) was added, and polycondensation was carried out at 280°C and under a vacuum of <100 Pa. After the intrinsic viscosity reached 0.65 dL / g, the material was discharged and pelletized to obtain recycled polyester chips (rPET). The rPET chips were dried and melt-spun to obtain recycled polyester filaments.
[0080] Compared with virgin PET fiber, the tensile strength and elongation at break of recycled PET fiber are as follows: the tensile strength of recycled PET fiber is 3.8 cN / dTex and the elongation at break is 23%; while the tensile strength of virgin PET fiber is 4.0 cN / dTex and the elongation at break is 26%. This proves that the TPA recovered by this invention is fully applicable to the industrial production of recycled fibers, truly realizing a closed-loop cycle. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for low-temperature, ambient-pressure depolymerization of waste polyester, characterized in that, include: Waste polyester raw materials are mixed with an inorganic alkaline aqueous solution, a quaternary ammonium salt phase transfer catalyst, and a compound solvent to form a reaction mixture; the compound solvent contains cyclic carbonates and alcohol compounds. Under conditions of temperature ≤110℃ and normal pressure, the reaction mixture is subjected to a depolymerization reaction to generate terephthalate and ethylene glycol.
2. The method for low-temperature atmospheric pressure depolymerization of waste polyester according to claim 1, characterized in that, The inorganic base is sodium hydroxide or potassium hydroxide; the cyclic carbonate is a five-membered cyclic carbonate.
3. The low-temperature atmospheric pressure depolymerization method for waste polyester according to claim 2, characterized in that, The five-membered cyclic carbonate is selected from at least one of propylene carbonate and ethylene carbonate; in the compound solvent, the mass ratio of the five-membered cyclic carbonate to the alcohol compound is 1.6:1 to 1.7:
1.
4. The low-temperature atmospheric pressure depolymerization method for waste polyester according to claim 1, characterized in that, The quaternary ammonium salt phase transfer catalyst is selected from one or more of hexadecyltrimethylammonium bromide, tetrabutylammonium bromide, and benzyltriethylammonium chloride.
5. The low-temperature atmospheric pressure depolymerization method for waste polyester according to claim 1, characterized in that, The alcohol compound is selected from at least one of ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, n-hexanol, ethylene glycol, 1,2-propanediol, and 1,3-propanediol.
6. The method for low-temperature atmospheric pressure depolymerization of waste polyester according to claim 1, characterized in that, The inorganic alkali aqueous solution has a mass percentage concentration of 10% to 15%; the mass ratio of the inorganic alkali in the inorganic alkali aqueous solution to the mass of the quaternary ammonium salt phase transfer catalyst is 50:1 to 80:
1.
7. The low-temperature atmospheric pressure depolymerization method for waste polyester according to claim 1, characterized in that, The depolymerization reaction is carried out at a temperature of 70℃ to 90℃ for 1 to 3 hours.
8. The low-temperature atmospheric pressure depolymerization method for waste polyester according to claim 1, characterized in that, The depolymerization reaction is carried out under ultrasonic conditions; Preferably, the ultrasonic conditions include: immersing the ultrasonic probe in the reaction solution and applying ultrasonic waves at a frequency of 20-30 kHz.
9. The low-temperature atmospheric pressure depolymerization method for waste polyester according to claim 1, characterized in that, The mass ratio of the waste polyester raw material to the total mass of the compound solvent, inorganic alkaline aqueous solution and quaternary ammonium salt phase transfer catalyst is 1:6 to 1:
12.
10. The method for low-temperature atmospheric pressure depolymerization of waste polyester according to claim 1, characterized in that, Also includes: The obtained terephthalate was acidified to obtain terephthalic acid; and After the depolymerization reaction is completed, the alcohol compounds are first separated by distillation, and then the cyclic carbonates are separated and recycled for the preparation of the compound solvent.
11. A method for preparing recycled polyethylene terephthalate, characterized in that, include: Terephthalic acid is obtained by the method of claim 10; The terephthalic acid was polymerized with ethylene glycol to obtain recycled polyethylene terephthalate. The recycled polyethylene terephthalate is then spun.
